Policy Discretion for Post-Disaster Rehabilitation and Reconstruction of Gunung Sinabung Eruption in Karo Regency in the Settlement Relocation Program - Dariyus Medi Sinulingga; Badaruddin Badaruddin; Robert Siregar (Budapest International Research and Critics University, 2021)
This research aims to reveal the Policy Discretion for Post-Disaster Rehabilitation and Reconstruction of Gunung Sinabung Eruption in Karo Regency in the Settlement Relocation Program. This study used qualtitative research. Disaster emergency factors (Emergency Response Status) and Humanitarian factors because the refugees have been living in temporary shelters (shelters) for ± 1.8 years in inadequate and inhumane living conditions are the driving forces for discretionary Rehabilitation and Reconstruction policies in the Settlement Relocation Program for disaster victims the eruption of Mount Sinabung, Karo Regency; Discretion of Post-Disaster Rehabilitation and Reconstruction of Mount Sinabung's Eruption in Relocation of Refugee Settlements is caused by a legal vacuum, because post-disaster development cannot be carried out in the Emergency Response phase where since September 2013 until now the Disaster Status of the Mount Sinabung Eruption is still in the Emergency Response phase.